Implementasi IoT Menggunakan Mikrokontroler NodeMCU ESP8266 Dalam Mengotomatisasi Mesin Untuk Penampungan Air - Jaka Sutresna; Fitri Yanti; Ahmad Musyafa (CV. Multi Kreasi Media, 2025)
The rapid development of Internet of Things (IoT) technology provides significant opportunities for creating intelligent, efficient, and adaptive automation systems, especially for domestic applications. One of these implementations includes automated water storage management and remote control of household electrical devices such as lighting systems. This research aims to design and implement a web-based automatic water tank control and lighting management system utilizing the NodeMCU ESP8266 microcontroller and ultrasonic sensors (HC-SR04). The ultrasonic sensor accurately measures the real-time water level inside the tank. Meanwhile, NodeMCU ESP8266 functions as a central controller that processes sensor data and establishes Wi-Fi connectivity for communication with a web platform developed using the XAMPP server, PHP, and MySQL. The designed system employs a hybrid operation mode combining automatic pump control based on sensor readings and manual lighting control through a responsive web interface. The testing results demonstrate that the system operates with high accuracy, exhibiting a sensor measurement error of approximately ±2 cm and system response times of less than 1 second. Additionally, testing of the communication stability between NodeMCU and the web platform indicated reliable and consistent connectivity without significant interruptions. The developed system offers ease of management, effective energy and water efficiency, and aligns with an innovative, adaptive, and flexible smart living concept suitable for various scenarios in modern household environments.